Charles Jenkins : The Silent Sisters - Book 3 - Dugoni, Robert (Thorndike, Maine : Center Point Large Print, 2022)
"After a harrowing escape from Russian agents on his last mission, Charles Jenkins thinks hes finally done with the spy game. But then the final two of the seven sisters - American assets who have been deep undercover in Russia for decades - cut off all communication with their handlers. Are they in hiding after detecting surveillance? Or have they turned and become double agents? Its Jenkinss duty to find out, but hes been added to a Russian kill list. It will require all of Jenkinss knowledge of spycraft - and an array of disguises - to return to the country undetected. But plans go awry his first night in Moscow when Jenkins gets involved in an altercation that ends in the death of the son of one of Russias most powerful organized-crime leaders. Pursued by mafia henchmen, Russian agents, and a particularly dogged Moscow police detective, Jenkins is determined to track down the final two sisters and get them to America - or die trying. As various forces close in, Jenkins fears this time he mightve pushed his luck too far."--
Keywords: United States -- Central Intelligence Agency -- Officials and employees; Fiction; Intelligence officers -- Fiction; Moles (Spies) -- Fiction; Undercover operations -- Russia (Federation); Moscow; Fiction; Fiction; Spy fiction; Thrillers (Fiction); Spy fiction; Thrillers (Fiction)